2021
DOI: 10.1109/tbme.2021.3063069
|View full text |Cite
|
Sign up to set email alerts
|

Rupture Detection During Needle Insertion Using Complex OCT Data and CNNs

Abstract: Soft tissue deformation and ruptures complicate needle placement. However, ruptures at tissue interfaces also contain information which helps physicians to navigate through different layers. This navigation task can be challenging, whenever ultrasound (US) image guidance is hard to align and externally sensed forces are superimposed by friction. Methods: We propose an experimental setup for reproducible needle insertions, applying optical coherence tomography (OCT) directly at the needle tip as well as externa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…5 For example, OCT probes have been used to study soft tissue characteristics by means of the morphology 6 or instrument interaction. 7 To enable robustness and miniaturization, OCT probes are often equipped with simple optics that generate A-scans, i.e., single-column depth images. A sequence of A-scans can be considered as M-scan.…”
Section: Introductionmentioning
confidence: 99%
“…5 For example, OCT probes have been used to study soft tissue characteristics by means of the morphology 6 or instrument interaction. 7 To enable robustness and miniaturization, OCT probes are often equipped with simple optics that generate A-scans, i.e., single-column depth images. A sequence of A-scans can be considered as M-scan.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we propose a method that can detect structures before physical contact occurs. We have recently shown that an optical coherence tomography (OCT) fiber embedded into an epidural needle can enable the detection of rupture events during needle insertions [10]. We now employ high resolution OCT needles to measure the distance to structures.…”
Section: Introductionmentioning
confidence: 99%